The Algebraic Galaxy of Simple Macroeconomic Models : A Hitchhiker's Guide - Tanner, Evan (IMF Working Papers; Working Paper ;, 2017)
Simple macroeconomic frameworks like the IS/LM have survived because they help us conceptualize complex problems while also providing 'back of the envelope' estimates of macroeconomic outcomes. Herein, a bare-bones New Keynesian extension of the IS/LM model yields solutions for core macro variables (output gap, inflation, interest rate, real exchange rate misvaluation)-expressed in percent. We then extend that standard model to also generate a corresponding set of demand-side elements-expressed in currency units. A key aim of the paper is to reconcile these two metrics in ways that also aid communication and intuition-including through IS/LM-style graphs.